The MAP2K2 Gene as Potential Diagnostic Marker in Monitoring Adalimumab Therapy of Psoriatic Arthritis - Krawczyk, Agata; Strzałka-Mrozik, Barbara; Juszczyk, Karol; Kimsa-Dudek, Magdalena; Wcisło-Dziadecka, Dominika; Gola, Joanna (Current pharmaceutical biotechnology, 2023)
MAP kinases are some of the cascades that are specialized in the cell's response to external stimuli. Their impaired functioning can be observed during the course of psoriatic arthritis. Currently, the best-known class of biological drugs is the inhibitors of the proinflammatory cytokine TNF-α, including adalimumab. The aim of this study was to assess changes in the expression of MAP kinase genes in patients with psoriatic arthritis treated with adalimumab, as well as to determine which of the analyzed transcripts could be used as a diagnostic or therapeutic target. An analysis was performed on the total RNA extracted from PBMCs of patients with psoriatic arthritis before and after three months of adalimumab therapy as well as from a control group. Changes in the expression of the mitogen-activated protein kinase genes were assessed using the HG-U133A 2.0 oligonucleotide microarray method, while the obtained results were validated using the real-time RT-qPCR method. Using the oligonucleotide microarray method, 14 genes coded for proteins from the MAPK group were identified with at least a two-fold change of expression in the control group and during adalimumab therapy. Validation of the results confirmed a statistically significant decrease in the transcriptional activity of the MAP2K2 gene in the group of patients three months after the administration of adalimumab relative to the control group. Adalimumab therapy alters the expression of MAPK-coding genes. The assessment of the number of MAP2K2 mRNA molecules can potentially be used in diagnostic analyses or in monitoring adalimumab therapy.